Evaluation of Financial Management of Sidoan Timur Village, Sidoan District: Transparency and Accountability in the Perspective of Governance of Sidoan Timur Village, Sidoan District, Parigi Moutong Regency, Central Sulawesi - Moh. Sagaf Said Hi. P. Malela; Kristyan Dwijosusilo; Kresna Adhi Prahmana; Dandy Patrija W (International Journal of Social Science and Humanity, 2025)
Village financial management is one of the key indicators in realizing effective village governance. However, in many villages, including Sidoan Timur Village, Sidoan District, Parigi Moutong Regency, Central Sulawesi, the practice of financial transparency and accountability still faces various obstacles. This study aims to assess the application of the principles of transparency and accountability in the financial management of Sidoan Timur Village, Sidoan District, Parigi Moutong Regency, Central Sulawesi, by referring to the perspective of village governance. The approach used is a qualitative method through case studies. Data were obtained through in-depth interviews, participatory observations, and review of official village documentation. Data analysis was carried out with the stages of data reduction, data presentation, and inductive conclusion drawing. The research findings reveal that village financial management has not fully implemented the principle of transparency, because financial information is not routinely published and administrative accountability is still formal, without active involvement from the community. In addition, the implementation of financial governance regulations has not been consistent at the operational level. In conclusion, the practice of transparency and accountability in Sidoan Timur Village needs to be strengthened by increasing the capacity of village officials, optimizing public information media, and empowering community participation. Further research is suggested to examine the comparison between several villages with a quantitative approach in order to obtain a broader picture of village financial management from a governance perspective.